2012
DOI: 10.1029/2012ja017542
|View full text |Cite
|
Sign up to set email alerts
|

The phases and amplitudes of gravity waves propagating and dissipating in the thermosphere: Application to measurements over Alaska

Abstract: [1] In a companion paper, we derived the high-frequency, compressible, dissipative polarization relations for gravity waves (GWs) propagating in the thermosphere. In this paper, we apply the results to nighttime thermospheric observations of a GW over Alaska on 9-10 January 2010. Using a vertically-pointed Fabry-Perot interferometer (FPI) at Poker Flat that measured vertical wind perturbations (w′) and two FPIs that measured the line-of-sight (LOS) velocities in four common volumes, we inferred a GW ground-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 77 publications
2
44
0
Order By: Relevance
“…Since we are only analyzing the published figures (not the data), we do not include error bars here. However, it is straightforward to include them [ Nicolls et al , 2012].…”
Section: Determination Of λH λZ and ωIr From In‐situ Satellite Obsementioning
confidence: 99%
See 2 more Smart Citations
“…Since we are only analyzing the published figures (not the data), we do not include error bars here. However, it is straightforward to include them [ Nicolls et al , 2012].…”
Section: Determination Of λH λZ and ωIr From In‐situ Satellite Obsementioning
confidence: 99%
“…Our second (more substantial) “test” is contained in our companion paper. Recently, high‐resolution, 3D neutral wind and temperature measurements using Fabry Perot observatories in Alaska have determined the phase shifts and amplitude ratios of a monochromatic GW observed there on 9–10 January 2010 [ Nicolls et al , 2012]. Using forward modeling, λ H and the direction of propagation were determined.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For typical horizontal scale sizes of the horizontal flow, and on time scales of hours, the magnitude of the vertical wind is not expected to be more than a few m/s [ Rishbeth et al , ; Smith , ]. However, measurements of persistent large vertical wind are not uncommon, especially at high latitudes [ Larsen and Meriwether , ; Nicolls et al , ]. Spencer et al [] first observed large, 80 m/s vertical winds at the AE‐C satellite, and ground‐based instruments have measured vertical winds at auroral latitudes of a few tens of m/s [ Rees et al , ; Ishii et al , ; Smith , ; Nicolls et al , ; Anderson et al , ; Larsen and Meriwether , , and references therein].…”
Section: Introductionmentioning
confidence: 99%
“…Only GWs with large λ z can propagate deep into the thermosphere ). Eventually, every GW dissipates in the thermosphere (Pitteway and Hines, 1963;Hines, 1973;Richmond, 1978;Hickey and Cole, 1988;Zhang and Yi, 2002;VF05;Walterscheid and Hickey, 2011;Vadas and Nicolls, 2012;Nicolls et al, 2012).…”
Section: Introductionmentioning
confidence: 99%